2010
DOI: 10.1002/ijc.24829
|View full text |Cite
|
Sign up to set email alerts
|

No association between fruit, vegetables, antioxidant nutrients and risk of renal cell carcinoma

Abstract: Previous epidemiologic studies that have examined the relationship between renal cell carcinoma (RCC) risk and intakes of plant foods and antioxidant nutrients have yielded inconsistent results. We therefore examined the associations between intakes of fruit, vegetables, carotenoids, flavonoids, vitamin E and vitamin C and RCC risk in the Alpha-Tocopherol, BetaCarotene Cancer Prevention (ATBC) Study cohort. At baseline, 27,062 male Finnish smokers aged 50-69 years completed a 276-item dietary questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 37 publications
4
48
2
Order By: Relevance
“…Aligned with our observations, previous case‐control,6, 34 individual cohort21 and pooled cohort22 studies have demonstrated significant associations between intake of carotenoids and RCC risk 34, 35, 36. However, other case‐control37 and cohort5, 7, 8, 14, 23 studies did not detect an association. Reasons for discrepancies in findings among dietary risk factor studies may be due to differences in the source populations, variations in dietary assessment methods, and varying degrees of recall bias between studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Aligned with our observations, previous case‐control,6, 34 individual cohort21 and pooled cohort22 studies have demonstrated significant associations between intake of carotenoids and RCC risk 34, 35, 36. However, other case‐control37 and cohort5, 7, 8, 14, 23 studies did not detect an association. Reasons for discrepancies in findings among dietary risk factor studies may be due to differences in the source populations, variations in dietary assessment methods, and varying degrees of recall bias between studies.…”
Section: Discussionsupporting
confidence: 87%
“…Aligned with these observations, previous studies demonstrated an association between increased intake of tocopherols with decreasing RCC risk for males and females, nonsmokers, and ever smokers 5, 36, 37, 38, 39, 40. In contrast, other studies reported associations of marginal or no significance between RCC risk and tocopherol intake 7, 8, 10, 14, 15, 41…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…73 Conversely, no association between dietary intake of fruits, vegetables, carotenoids, flavonoids, vitamin E, and vitamin C and the risk of developing RCC was found in the ATBC (AlphaTocopherol, Beta-Carotene Cancer Prevention) study (27 062 male Finnish smokers, 255 cases followed up for 19 years). 74 Similarly, in the NLCS (Netherlands Cohort Study) on diet and cancer, van Dijk and colleagues reported no association between carotenoid, vitamin or supplemental vitamin intake and the risk of RCC. 75 Thus, although metabolic alterations in oxidative stress pathways and fat metabolism are definitely part of the RCC genotype and phenotype, the available data do not support a role for dietary manipulations in altering the risk of developing RCC.…”
Section: Effect Of Diet On Rccmentioning
confidence: 99%